Differences in risk indicators associated with electronic cigarette use and tobacco smoking among adolescents and young people in Nigeria - Morenike Oluwatoyin Folayan; Maha El Tantawi; Afolabi Oyapero; Omolola Alade; Yewande Adeyemo; Heba Jafar Sabbagh; Elizabeth O Oziegbe; Bamidele Olubukola Popoola; Maryam Quritum (BMJ Open Respiratory Research, 2022)
Introduction The study determined the proportion of adolescents and young persons (AYP) in Nigeria who use e-cigarettes and smoke tobacco; and identified factors associated with the use of e-cigarettes and tobacco smoking.Methods AYP aged 11–23 years were recruited to participate in an online survey. The independent variables were respondents’ health, HIV and COVID-19 status and their level of anxiety. The dependent variables were tobacco smoking and use of e-cigarettes. Binary logistic regression was used to determine the associations between the dependent and independent variables after adjusting for confounders (age, sex, educational level and vulnerability status).Results There were 2206 respondents of which 568 (19.8%) used e-cigarettes and 787 (27.4%) smoked tobacco. Individual (18–23 years, having a health condition, high anxiety and being vulnerable) and familial (having father, mother, siblings or friends who used e-cigarettes) factors were associated with both the use of e-cigarettes and tobacco smoking. Tobacco smoking was a significant risk indicator for e-cigarettes use and vice versa. COVID-19 infection (adjusted OR, AOR: 3.602) and living with HIV (AOR: 1.898) were associated with higher odds of using e-cigarettes. Males (AOR: 1.577), 15–17 years (AOR: 6.621) and moderate anxiety (AOR: 2.500) were associated with higher odds of tobacco smoking. AYP with health conditions had higher odds of using e-cigarettes (AOR: 1.514) while AYP with moderate anxiety had lower odds of using e-cigarettes (AOR: 0.627).Conclusion The proportion of AYP in Nigeria who used e-cigarettes and smoked tobacco is high. Public health interventions that target the common risk factors for e-cigarettes use and tobacco smoking among AYP in Nigeria are urgently needed.